Implementasi Kurikulum Merdeka dalam Pembelajaran Ilmu Pengetahuan Sosial di SMP Negeri 2 Gebog - Fikri, Rizal Haikal; Lestari, Puji (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
The Merdeka Curriculum is a form of continuation and simplification of the 2013 Curriculum, which is the government's breakthrough as an effort to improve the condition of Indonesian education. SMP Negeri 2 Gebog faces challenges in implementing the Merdeka Curriculum, especially in social studies learning. Even though various forms of socialization and training have been provided, there are still teachers who do not fully understand the stages of curriculum implementation, which include Diagnostic Assessment, Learning Planning, and Learning Implementation. In addition, the challenges of adapting to curriculum changes, both on the part of teachers and students, are factors that affect the effectiveness of the implementation of the Merdeka Curriculum. The purpose of this study is to explain the curriculum implementation stage in social studies learning, including Diagnostic Assessment, Learning Planning, and Learning Implementation. The method used in this research is a qualitative method using qualitative data whose data sources are obtained from seventh grade social studies teachers at SMP Negeri 2 Gebog. Data collection techniques used in this research are observation, interview, and documentation. The results of this study explain overall that the implementation of Merdeka Curriculum in Social Studies Learning at SMP Negeri 2 Gebog is in accordance with the reference stages of learning implementation in Merdeka Curriculum, including Diagnostic Assessment, Learning Planning, and Learning Implementation.